Duet playing in dementia care: a new therapeutic music technology. - Nicol, Jennifer; Loehr, Janeen; Christensen, Justin; Lang, Jennifer; Peacock, Shelley (Disability & Rehabilitation: Assistive Technology, 2024)
Purpose: Supporting the relational worlds of people living with dementia, especially the spousal dyad, is a growing focus in dementia care as is advancing the therapeutic use of music in dementia care. This paper describes a mixed-methods, multi-phase, iterative research study designed to develop the Music Memory Makers (MMM) Duet System, a novel therapeutic music technology, that allows non-musicians to play a personalized repertoire of songs arranged as duets. Methods: Following a pilot phase to iteratively assess and refine the MMM Duet System for recreational and therapeutic purposes, multiple sources of data were used to investigate five older spousal dyads' experiences with the system, two couples living with dementia and three who were not. We assessed perceptions of task difficulty, joint agency, and enjoyment as well as therapeutic benefits associated with enhancing the spousal relationship and sense of couplehood. Results: Findings suggest playing meaningful songs together is an enjoyable interactive activity that prompts musical reminiscence, involves joint agency, and supports relationship continuity within a relational, positive approach to dementia care. All couples mastered the task, none evaluated it as "very challenging," and positive couple interactions were evoked, commonly before and after playing the duets. Conclusions: The MMM Duet System is recommended for further research and development as an innovative way to support couples living with dementia with commercial implications, and as a new music technology suitable for use as a research tool. IMPLICATIONS FOR REHABILITATION: Music making is an engaging, rewarding activity promoting social bonding and wellbeing that with technology innovation, can be extended to non-musicians and people with differing skills, abilities, and preferences. The MMM Duet System is a promising new music technology that supports the relationship of people living with dementia and their spousal caregivers by encouraging relationship continuity and sense of couplehood. Supporting caregivers enables people with dementia to remain longer in their homes and communities. Practical suggestions are offered to develop music technology suitable for use by older adults and people living with dementia, e.g., involving participants who live with dementia, assembling interdisciplinary research teams, adopting iterative, participant-focused approach.